PENDIDIKAN AGAMA ISLAM TERPADU PADA SMPIT BINA UMAT YOGYAKARTA - Soemanto Soemanto (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
Around the 2000s many institutions labeled as Islamic Integrated Schools (Sekolah Islam Terpadu/SIT) emerged. They were quite attractive to the public. One of the concepts of Integrated Islamic School is a one that uses a combined approach of general and religious educations into a fi ne integration in terms of curriculum, teaching methods, education of Aqliyah (rational), Ruhiyah (spiritual) and jasadiyah (physical). This study using qualitative approach aims to describe what and how the integration model in Islamic Junior Secondary Education (SMPIT) Bina Umat are all about. The fi ndings suggest that there are at least four components that comprise essential elements of integration in SMPIT Bina Ummah. The fi rst is the integration with the environment. The second is the integration in terms of curriculum aspects. The third is the integration with traditional model of boarding school education. And the fourth is the integrated learning both inside and outside the classroom.